1997
DOI: 10.1007/s004649900333
|View full text |Cite
|
Sign up to set email alerts
|

Does laparoscopy increase bacteremia and endotoxemia in a peritonitis model?

Abstract: Laparoscopy does not increase bacteremia and intraperitoneal abscess formation compared to laparotomy in an animal model of peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
34
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 13 publications
5
34
0
1
Order By: Relevance
“…Only a few controversial experimental data exist with regard to the effect of pneumoperitoneum on bacteremia and physiological changes in sepsis [15][16][17][18][19]. The aim of this study was to evaluate the effect of CO 2 pneumoperitoneum on endotoxemia and the proinflammatory cytokine response in intraperitoneal sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few controversial experimental data exist with regard to the effect of pneumoperitoneum on bacteremia and physiological changes in sepsis [15][16][17][18][19]. The aim of this study was to evaluate the effect of CO 2 pneumoperitoneum on endotoxemia and the proinflammatory cytokine response in intraperitoneal sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that these values were significantly low in the CO 2 pneumoperitoneum-induced group, and it was reported that CO 2 pneumoperitoneum reduces inflammatory response in the peritoneum in the case of sepsis, when compared to open surgery. [22] In another study on pigs, it was found that the increase in the leukocyte and macrophage percentage was significantly low. Besides the low inflammatory response, it was observed that CO 2 pneumoperitoneum does not promote the bacteriemia or produce metabolic and hemodynamic problems in acute peritonitis.…”
Section: Discussionmentioning
confidence: 95%
“…İpek et al, [14] having studied the effects of CO 2 pneumoperitoneum on the degree of bacteriemia and peritonitis, observed that 1 hour after cecostomy, peritonitis severity scores were higher in the CO 2 pneumoperitoneum group than in the control group, but 3 to 6 hours after cecostomy, there was no difference between the groups. Jacobi et al, [22] in their experimental study investigating whether or not the laparoscopic interventions augment the bacteriemia and endotoxemia in the presence of peritonitis, reported that the laparoscopic interventions do not augment the bacteriemia and abscess processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model of long-term sepsis obtained by gastric perforation in pigs, a significant increase in the extent and severity of peritonitis and bacteremia was observed after treatment by videolaparoscopy 3 . On the other hand, in another study using a model of peritonitis induced by inoculation of feces into the peritoneal cavity of rats, laparoscopy was not associated with a significant increase in bacteremia 4 . Among the limitations of videolaparoscopic access for the treatment of peritonitis, the most significant is the possibility that high intra-abdominal pressure in the presence of pneumoperitoneum will induce bacterial translocation, along with the attendant bacteremia and death…”
Section: Introductionmentioning
confidence: 84%